2021
DOI: 10.1016/j.jhepr.2021.100326
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes following resection of hepatocellular adenomas with small foci of malignant transformation or malignant adenomas

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…A recent study of malignancy in HCA cases reported a surprisingly high frequency of malignant transformation of IHCA without b-catenin mutation. 66 However, these findings could not be replicated by another recent study. 67…”
Section: H C Amentioning
confidence: 73%
See 2 more Smart Citations
“…A recent study of malignancy in HCA cases reported a surprisingly high frequency of malignant transformation of IHCA without b-catenin mutation. 66 However, these findings could not be replicated by another recent study. 67…”
Section: H C Amentioning
confidence: 73%
“…A subset of IHCAs contain an additional cadherin‐associated protein β1 gene ( CTNNB1 ) mutation and represent another HCA subtype, β‐catenin‐mutated IHCA (b‐IHCA) (see below), which may progress to HCC. A recent study of malignancy in HCA cases reported a surprisingly high frequency of malignant transformation of IHCA without β‐catenin mutation 66 . However, these findings could not be replicated by another recent study 67 …”
Section: Hca Classificationmentioning
confidence: 93%
See 1 more Smart Citation
“…on long-term outcomes following resection of hepatocellular adenoma with malignant transformation (MT-HCA). 1 …”
mentioning
confidence: 99%
“…We are pleased to address the issues they raised regarding our study, which concerns a matched case-control study comparing the long-term outcome after liver resection for HCA with malignant transformation (MT-HCA) to hepatocellular carcinoma (HCC) developed on normal liver-parenchyma. 2 …”
mentioning
confidence: 99%